2021
DOI: 10.1055/s-0041-1734385
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients of Chronic Low Back Pain have Psychological Comorbidities?

Abstract: Background Individuals with chronic pain have been reported to have an increased incidence of psychological morbidities. We aimed to examine the prevalence of anxiety, depression, disability, alexithymia, insomnia, and sleep quality in patients having chronic low back pain (LBP) and study their association with the severity of pain and any disability arising from it. Methods This descriptive study was conducted in a tertiary care teaching hospital setting. Fifty adults with nonspecific LBP of > 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
4
12
1
Order By: Relevance
“…However, among individuals with co-occurring insomnia and mental distress, the association was not significant. The prevalence of insomnia has been estimated to range between ∼5% and ∼15% [44][45][46] in the general population and between ∼30% and ∼50% among individuals with LBP [47][48][49]. In our study, the prevalence of insomnia among individuals with LBP during the previous year was 36.3%, which is of a similar magnitude to previous estimates [47][48][49].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, among individuals with co-occurring insomnia and mental distress, the association was not significant. The prevalence of insomnia has been estimated to range between ∼5% and ∼15% [44][45][46] in the general population and between ∼30% and ∼50% among individuals with LBP [47][48][49]. In our study, the prevalence of insomnia among individuals with LBP during the previous year was 36.3%, which is of a similar magnitude to previous estimates [47][48][49].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of insomnia has been estimated to range between ∼5% and ∼15% [44][45][46] in the general population and between ∼30% and ∼50% among individuals with LBP [47][48][49]. In our study, the prevalence of insomnia among individuals with LBP during the previous year was 36.3%, which is of a similar magnitude to previous estimates [47][48][49]. The general prevalence of depression has been reported to be ∼5% [50][51][52] and the prevalence of mental distress among people with LBP ∼14% [49,53].…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain has been linked to poor sleep quality or sleep disorders in previous research [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the clinical variables, a Dutch study showed that pain intensity was significantly associated with anxiety symptoms in CLBP patients, but the association between pain duration and anxiety symptoms was not observed ( 16 ). A study conducted in India did not find a significant association between the severity of pain and anxiety ( 17 ). Families are the primary source of social support for CLBP patients, a protective determinant of mental health.…”
Section: Introductionmentioning
confidence: 99%